A taxonomic revision of the genus Florestina (Asteraceae, Bahieae) - Soto-Trejo, Fabiola; Schilling, Edward E.; Oyama, Ken; Lira, Rafael; Dávila, Patricia (Phytotaxa, 2016)
We present a taxonomic revision of Florestina (Asteraceae, Bahieae), a genus that includes annual herbaceous species that occur mostly in arid and semiarid regions of Mexico. A key is provided for the six species of the genus. Taxon descriptions include geographic distribution, habitat, phenology and taxonomic notes on each species. Florestina simplicifolia is reduced to be a synonym of F. pedata, and F. liebmannii is reduced to a synonym of F. tripteris. The lectotype is designated for F. pedata.